Analysis of Purchase Decisions for MSME-Processed Functional Food Products in the Jabodetabek Region: A Model Testing of the Effects of Functional Value, Brand Image, Electronic Word of Mouth, and Local Wisdom-Based Marketing - Sihotang, Pirnanti; Amelia, Tifa Noer (Dinasti Publisher, 2026)
The Influence of Functional Value, Brand Image, Electronic Word of Mouth, and Local Wisdom-Based Marketing on Purchase Decisions for MSME Functional Food Products in the Jabodetabek Region. This study was motivated by the increasing competition among MSME functional food products in urban areas, which necessitates marketing strategies grounded in rational, digital, and cultural value dimensions. The research aims to analyze the effects of functional value, brand image, electronic word of mouth communication, and Local Wisdom-Based Marketing on consumers’ purchase decisions. An explanatory quantitative approach was employed, utilizing a survey of 240 consumers of MSME functional food products in the Jabodetabek region selected through purposive sampling. The data were analyzed using Structural Equation Modeling based on Partial Least Squares. The findings indicate that all variables exert a positive and significant influence on purchase decisions, with electronic word of mouth emerging as the most dominant variable, followed by Local Wisdom-Based Marketing, brand image, and functional value. These results affirm that purchase decisions are shaped by a combination of rational, social, symbolic, and cultural stimuli processed through consumers’ cognitive and affective evaluations. This study contributes to the development of MSME marketing strategies through the integration of functional, digital, and local cultural values.